2017
DOI: 10.3855/jidc.8934
|View full text |Cite
|
Sign up to set email alerts
|

Critical points and the presence of pathogenic bacteria in iced beverage processing lines

Abstract: Introduction: Ice can be contaminated by pathogenic bacteria. This study aimed to identify critical points in iced beverage production and distribution lines to examine the presence of pathogenic bacteria in a beverage and its processing environment, as well as when water and ice used as main ingredients. Methodology: The critical points were determined using the principles of Hazard Analytical Critical Control Point (HACCP) to analyze each processing and distribution step from the survey. Samples collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
1
6
0
1
Order By: Relevance
“…Labile toxin of ETEC was the most common virulence factor found in food samples such as water and ice. The results of this study are supported by research conducted by Nababan et al (2017) who found that 0.7% of icebased beverages samples from three provinces in Indonesia were contaminated by ETEC. Kamaruzaman et al (2017) found out that the source of contamination on ice-based beverages comes from ice cubes that added to ice-based beverages.…”
Section: The Prevalence Of Pathogenic E Colisupporting
confidence: 83%
See 1 more Smart Citation
“…Labile toxin of ETEC was the most common virulence factor found in food samples such as water and ice. The results of this study are supported by research conducted by Nababan et al (2017) who found that 0.7% of icebased beverages samples from three provinces in Indonesia were contaminated by ETEC. Kamaruzaman et al (2017) found out that the source of contamination on ice-based beverages comes from ice cubes that added to ice-based beverages.…”
Section: The Prevalence Of Pathogenic E Colisupporting
confidence: 83%
“…Coliform and E. coli could be used as an indicator of the organism for fecal contamination in hygienic practices. The previous studies also already reported the presence of pathogenic bacteria such as E. coli, Salmonella spp., and Vibrio cholerae in ice (Waturangi et al, 2012a, Waturangi et al, 2012b, Nababan et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…During the period from November to December 2014, samples of water, ice cubes, frozen drinks and ice drinks were analyzed in three Indonesian cities (City A, City B and City C) to evaluate the presence of E. coli, S. aureus, Salmonella spp. and Vibrio cholerae from ice producers/manufacturers, distributors and vendors of iced beverages [16]. In particular, the presence of pathogens was assessed in three lines of drinks: with crushed ice in a plastic bag (line 1), with crushed ice in blocks (line 2) and with ice crystals (line 3).…”
Section: Bacterial Contaminationmentioning
confidence: 99%
“…In water used for the preparation of frozen drinks and ice production, V. cholerae was found in 0.7% of the samples, but on 2.12% of the tools used in ice distribution and production. Staphylococcus aureus was found on 2.02% of ice distribution and production equipment surfaces and 5.05% of production and distribution workers' hands [16].…”
Section: Bacterial Contaminationmentioning
confidence: 99%
“…Hasil penelitian menunjukkan bawa sebanyak 37,5% es krim di Medan tercemar E. coli (13) sedangkan studi lain menemukan 100% jus buah di Tembalang tercemar mikroba yang sama (14). Lebih spesifik, penelitian menunjukkan 6,34% minuman es positif mengandung E. coli dan 0,7% diantaranya dari jenis E. coli toksigenik atau Enterotoxigenic Escherichia coli (ETEC) (15). Selain itu, studi sebelumnya menyatakan bahwa 4% minuman es di Kota Bogor tercemar E. coli jenis Enterohaemorrhagic E. coli (EHEC) (16).…”
Section: Bahasan Pola Konsumsi Jajanan Minuman Esunclassified